Avaliação sobre a presença de hidrocarbonetos policíclicos aromáticos (HPAs) em formulações farmacêuticas injetáveis - Moura, Juliane Froncheti de (2009)
Polyciclic Aromatic Hydrocarbons (PHAs) are a family of compounds which contain two or more condensed aromatic rings. These substances, including the oxygenate and nitrogenate derivates, are widely spread in the environment, being found in several locations. A great number of PAHs, with similar structural and physicochemical characteristics, which are known by their carcinogenic and mutagenic properties, are distributed in the environment. In this study the presence of PAHs in carbon black, rubbers used as closure in medication containers, as well as in some pharmaceutical formulations (amino acid and lipid solutions for parenteral nutrition and some injectable drugs) was investigated by high performance liquid chromatography. The origin of PAHs in rubbers and in pharmaceutical products stored in containers with rubber closures is the carbon black used as pigment. For the analysis, PAHs were extracted from the carbon black itself and from different types of rubber closures with acetone. The determination in the pharmaceutical formulations demanded a previous solid phase extraction of the PAHs, using polystyrene columns. The extraction was optimized with individual solution of each formulation investigated. The results showed that all analyzed rubbers were contaminated by PAHs. The levels were within 0.12 mg g-1 for Benzo(a)Pyrene and 5.64 mg g-1 for Benzo(ghi)Perylene. Among the pharmaceutical products, amino acid solutions presented levels between 0.02 mg L-1 for Benzo(a)Pyrene and 0.21 mg L-1 for Pyrene, and lipid emulsions 0.07 mg L-1 and 0.19 mg L-1 for the same PAHs. Among the injectables, the contamination ranged between 0.06 mg L-1 and 0.031 mg L-1 for the Benzo(a)Pyrene.